Indonesian students’ perceptions towards AI-based learning in mathematics - Soesanto, Robert Harry; Dirgantoro, Kurnia Putri Sepdikasari; Priyanti, Neng (Journal on Mathematics Education, 2022)
The pandemic has indeed provided students and teachers worldwide with the experience of technology-infused teaching. Even though the pandemic is almost over, the utilization of technology in mathematics education is still needed and inseparable. Relying on cross-sectional design and phenomenological approach, this research investigates senior high school students' perceptions towards AI-based learning, particularly about their understanding and suggestions towards AI-based learning in mathematics in the context of post-pandemic. The participants of the study were 107 students coming from several islands in Indonesia, ranging from grade 10-12, with an age interval of 15-18 years old. The instruments used were the questionaries with open-ended questions in Microsoft forms distributed to mathematics teachers in several WhatsApp groups. The data were then analyzed through a multistage descriptive and pattern coding process. The findings showed that students need to be facilitated with AI, which can display understandable visualization and provide guidance to solve mathematical problems. It is expected that the present study's findings offer researchers in Indonesia and abroad to disseminate and/or implement AI learning in the form of Intelligent Tutoring Systems.